Interfacial engineering in functional materials for dye-sensitized solar cells - Pandikumar, Alagarsamy; Jothivenkatachalam, Kandasamy, 1973-; Bhojanaa, Karuppanapillai B., 1995- (Wiley, 2020)
"Solar energy has paved the way as an alternative to fossil fuels for present and future energy demands. Dye-sensitized solar cells (DSSC) are one of the most promising techniques to harvest solar energy and convert it into electrical energy because of their ease of production, low cost, flexibility, relatively high conversion efficiency, and low toxicity to the environment. DSSCs consist of components such as electrolytes, dyes, counter electrodes, and photoanodes. Among these, the photoanode plays a vital role and serves as the support for dye molecules and transport photo-excited electrons"--